Pengaruh Kesadaran Wajib Pajak dan Tingkat Pendidikan Terhadap Kepatuhan Wajib Pajak Orang Pribadi yang Melakukan Pekerjaan Bebas di Kecamatan Riung (Studi Pada Masyarakat Riung Kabupaten Ngada Nusa Tenggara Timur) - Nafisa Insha; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Tax compliance is a condition where taxpayers fulfill all tax obligations and exercise their tax rights. The purpose of this study is to determine whether taxpayer awareness and education level have a significant influence on individual taxpayer compliance who does free work in Riung District. The sampling technique in this study used a purposive sampling method where the data source was primary data obtained from the distribution of questionnaires as a research instrument. Data analysis used multiple linear regression. The results showed that taxpayer awareness had a positive and significant effect on taxpayer compliance while education level had no effect on taxpayer compliance, taxpayer awareness and education level simultaneously affected taxpayer compliance.Keywords: Taxpayer awareness, education level and taxpayer compliance